2022
DOI: 10.1002/jcc.26967
|View full text |Cite
|
Sign up to set email alerts
|

Conformational distributions of helical perfluoroalkyl substances and impacts on stability

Abstract: Per-and polyfluoroalkyl substances (PFAS) have been widely used the past 70 years in numerous applications due to their chemical and thermal stability. Due to their robust stability, they are environmentally recalcitrant which made them one of the most persistent environmental contaminants. In addition to strong C F bond strength, oleophobicity, hydrophobicity, and high reduction-oxidation (redox) potential of PFAS has led to their inefficient degradation by traditional means. A characteristic of their structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To determine the effect of not searching for the global minimum, 20 PFASs were used to compare the calculated C–F BDEs from the lowest energy conformers versus those obtained from helical conformers (Scheme b). The helical conformation was chosen because the preferred state of a long-chain PFAS is where the C–F bonds are arranged in a helix . The helicity arises from a 17–20° twist in the C–C–C–C dihedral angle of the carbon backbone from the all-trans 180° observed in hydrocarbons (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of not searching for the global minimum, 20 PFASs were used to compare the calculated C–F BDEs from the lowest energy conformers versus those obtained from helical conformers (Scheme b). The helical conformation was chosen because the preferred state of a long-chain PFAS is where the C–F bonds are arranged in a helix . The helicity arises from a 17–20° twist in the C–C–C–C dihedral angle of the carbon backbone from the all-trans 180° observed in hydrocarbons (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The helical conformation was chosen because the preferred state of a long-chain PFAS is where the C−F bonds are arranged in a helix. 55 The helicity arises from a 17− 20°twist in the C−C−C−C dihedral angle of the carbon backbone from the all-trans 180°observed in hydrocarbons (Figure 3a). The corresponding radical product geometry was obtained by deleting the relevant fluorine atom from the PFAS and then reoptimizing at the M06-2X/6-31+G(d) level of theory.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The longer PFCAs adopt a helicity to the carbon backbone, which is increasingly pronounced as the chain length increases and more pronounced in the neutral than in the ions. The effects of helicity in PFCA have been explored elsewhere . Similar helicity in n -perfluoroalkanes has been attributed variously either to electrostatic interactions or to hyperconjugation. , The orientation of the carboxylic head group varies relative to the carbon backbone.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of helicity in PFCA have been explored elsewhere. 36 Similar helicity in n-perfluoroalkanes has been attributed variously either to electrostatic interactions or to hyperconjugation. 37,38 The orientation of the carboxylic head group varies relative to the carbon backbone.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Unlike PFPrA, PFCAs with a chain length greater than C4 can exhibit a stable helical conformation, characterized by a torsional twist in the central F−C−C−F or C−C−C−C dihedral angle. 66 To minimize the complexities of performing conformational sampling, only the straight-chain conformers were considered in this study; however, the impact of conformational isomerism on the calculated properties reported here is currently underway and will be reported in a future study. Another chain length effect is the "1,2-F atom rearrangement" that could occur in perfluoroalkyl radicals resulting from cleavage of the carboxyl group.…”
Section: Mechanistic Insights For Pfasmentioning
confidence: 99%